Cyberbullying and traditional bullying involvement among heterosexual and non-heterosexual adolescents, and their associations with age and gender. (June 2018) - DeSmet, A.; Rodelli, M.; Walrave, M.; Soenens, B.; Cardon, G.; De Bourdeaudhuij, I.
Abstract: Introduction: Traditional (offline) bullying and cyberbullying involvement are associated with severe psychosocial problems. Non-heterosexual (LGBQ) youth are more often victimized by traditional bullying than heterosexual (non-LGBQ) youth, but little research is available on LGBQ youth's cyberbullying victimization and perpetration rates. Moreover, rates may differ by youth's age and gender, and victimization may be higher for sexual forms of cyberbullying. Method: A cross-sectional, school-based survey was conducted in Flanders, Belgium among 1037 adolescents aged 12–18 years. Traditional and cyberbullying involvement were measured using validated single items for each type of involvement (victimization, perpetration), and complemented with items on specific types of cyberbullying victimization (by messaging and posts; by sexual images; by personally embarrassing images). Sexual orientation was determined based on sexual attraction. Logistic regression analyses were conducted, corrected for age and gender. Results: LGBQ youth were more often victimized by traditional victimization than non-LGBQ youth and more often perpetrator of cyberbullying. No gender differences were found, and no increased rates of traditional bullying perpetration were noted once interaction effects with age and gender were taken into account. A significant interaction effect was found with age for traditional victimization, cyberbullying victimization, and cyberbullying victimization by messaging/posts and by sexual images: these prevalence rates were higher among older LGBQ youth but decreased or remained stable among non-LGBQ youth with age. Conclusion: This study highlights the need for tailored prevention and intervention programs specific for LGBQ youth in late adolescence, whereas most current programs are targeted at early adolescence when there is a peak in victimization for the general population. Highlights: Non-heterosexual youth are more often victim of traditional bullying. Non-heterosexual youth had increased rates of cyber- but not of traditional perpetration. (Cyber-)victimization among non-heterosexual youth increased with age. (Cyber-)victimization did not increase with age among heterosexual youth. Targeted prevention programs for non-heterosexual youth are needed at later age.